Perturbation Analysis of Population Growth Rates in Taiwan - Shun-Chieh Hsieh (Discrete Dynamics in Nature and Society)
The total fertility rate in Taiwan has fallen below 1.3 since 2003. The objective of the study is to use perturbation analysis with census data from 1992 to 2017 to identify which demographic parameters are most important to target for population management. The research shows that the fertility of older ages plays an important role for declining population in Taiwan. From a practical viewpoint, population management policy having a substantial impact on the survival of prereproductive females and the fertility of order females is likely to produce the most dramatic change in population trends. Therefore, the perturbation analysis is useful in understanding the relative importance of vital rates to increase management effectiveness.